Percepção dos profissionais de nível superior da atenção primária quanto ao desenvolvimento de ações de saúde do trabalhador no SUS em Minas Gerais - Claudia Vasques Chiavegatto (2010)
Introduction: So far, training on occupational health in Brazil has been prepared by occupational health professionals. Nevertheless, for a deep learning, according to the prescriptions of the National Permanent Health Education Policy, it is important to consider the needs and thoughts of the primary care professionals. Objective: To identify the opinion of graduate health professionals working on public primary health care services in Minas Gerais, regarding occupational health. Methods: Transversalquali-quantitative study divided into 2 stages, conducted in different health regions of the state of Minas Gerais in 2009. Stage 1 consisted of a structured survey answered by 358 doctors, nurses and dentists who were taking a post graduate course offered by the Federal University of Minas Gerais on Primary and Family Health Care. Stage 2 consisted of a Delphi study with participation of 26 health professionals who took theoccupational health program, which is optional within the course. Both stages results were analyzed with SPSS 13.0 version. Results: Professionals recognize their role in the development of the occupational health actions presented in stage 1. In stage 2, they spontaneously cite a great number of actions they see as their responsibility, going beyond the actions prescribed by official training material. However, data analysisindicates that primary health care professionals develop these actions in a frequency under expectation considering the high level of agreement on its importance and the recognition of the role they play in their development. According to these professionals, reasons for this lie on the difficulties faced, like lack of effective professional training, planning, financial and political support, prioritization of these actions by the Ministryof Health, deficient referring routes, great number of activities under theirresponsibility, etc. Conclusions: Occupational health actions are already part of primary health care routine. It is now necessary to provide these professionals with appropriate tools, technical and political support so as to improve effectiveness and impact of these actions. Some recommendations are made. Professional training is important, but to promote a real change in its development by primary health care, theremust be a national political discussion involving authorities, occupational health reference services and regional health management.